Thermoelectric properties of Ge/Si heterostructures: A combined theoretical and experimental study - Fiedler, Gregor; Nausner, Lukas; Hu, Yang; Chen, Peixuan; Rastelli, Armando; Kratzer, Peter; et al. (physica status solidi (a), 2016)
We present a combined experimental and theoretical investigation of the thermoelectric properties of p-doped Ge/Si superlattices grown on Si(001) substrates by molecular beam epitaxy. Electrical conductivity is measured both in the direction parallel and perpendicular to the interfaces by means of a modified transfer length method. Electronic transport is strongly anisotropic, with the cross-plane conductivity being about five times lower than in plane. This result is in very good agreement with the theoretical predictions based on the tight-binding method combined with the Boltzmann equation applied to the experimentally investigated structure. The cross-plane thermal conductivity of doped superlattices is measured with the differential 3ω method and compared with that of undoped superlattices and alloys with similar average Ge content. The comparison reveals that superlattices have strongly reduced thermal conduction compared to alloys, and that doping increases their thermal conductivity by about 50%. Considering the used doping level, this increase appears surprising. The Seebeck coefficient of the structures is addressed theoretically and displays a less pronounced anisotropy compared to the electric conductivity. Combined with the knowledge of the other thermoelectric parameters, we conclude that, while p-doped Si/Ge superlattices may be used as model systems for the investigation of thermoelectric transport in nanostructured materials, their relevance for application is limited.
CRIS-Team Scopus Importer:2023-03-20
Keywords: electrical conductivity; Ge/Si; Superlattices; thermal conductivity; thermoelectricity; tight-binding calculations